PERAN BINTARA PEMBINA DESA (BABINSA) DALAM MENUNJANG KETERTIBAN DAN KEAMANAN MASYARAKAT DI DESA PENGASI BARU KECAMATAN BUKIT KERMAN: TESA OCDIYANA, SH - Ocdiyana, SH, Tesa (Qawwam : The Leader's Writing, 2021)
The title of this research is the role of the Village Guidance Officer (BABINSA) in Supporting Public Order and Security in Pengasi Baru Village, Bukit Kerman District. This study aims to determine the role of the Village Guidance Officer (BABINSA) in Supporting Public Order and Security in Pengasi Baru Village, Bukit Kerman District. This research uses a qualitative research approach with qualitative descriptive research type, this research is conducted in order to explain objectively and rationally about the object of research. Sources of data in this study were 9 people. What is taken is primary data and secondary data. The data collection technique was carried out by means of in-depth interviews, namely data collection techniques carried out by researchers to obtain information verbally through question and answer, who faced directly with a number of informants who could provide information related to research problems. That the routine activities carried out by babinsa are currently quite influential in their implementation. In realizing the professionalism of the TNI AD, every soldier should increase knowledge and improve higher education levels. The results of this study are expected to help contribute to the thoughts of the author for all parties, especially for the village of Pengasi Baru and members of the babinsa.